ANALISIS KETERAMPILAN GERAK DASAR LOKOMOTOR DALAM PEMBELAJARAN PJOK DI SDK NGEDUKELU - Skolastika Mariana Suri; Gabriel Ruju; Yanuarius Ricardus Natal (Cermat : Jurnal Cendekiawan dan Riset Multidisiplin Akademik Terintegrasi, 2026)
ABSTRACT This study aims to analyze students’ fundamental locomotor movement skills in Physical Education, Sports, and Health (PJOK) learning at SDK Ngedukelu. The method used is descriptive qualitative analysis involving observation, fundamental movement skill tests, and assessment rubrics as the main instruments. The study was conducted in two learning cycles that integrated cooperative learning models and modified games. The results show an improvement in students’ fundamental locomotor movement skills from the beginning to the end of the study, particularly in walking, running, and jumping movements. This improvement was driven by the implementation of more interactive and enjoyable learning activities, as well as the use of appropriate learning media. The study recommends that game-based learning methods be applied regularly to support the development of fundamental locomotor movement skills of elementary school students.